Toxicological and antifertility investigations of oleanolic acid in male vervet monkeys (chlorocebus aethiops) - Mdhluli, Mongezi (University of the Western Cape, 2021)
Philosophiae Doctor - PhD === Introduction: Plant extracts and herbal preparations are often marketed as natural and safe alternatives to conventional medicines for the prevention and treatment of a variety of ailments, without proof of efficacy and safety. Cardiovascular, hematopoetic, hepatic and renal impairment resulting from the use of conventional drugs is widely acknowledged. However, there is less awareness of the potential toxicity of herbal preparations and other botanicals, many of which are widely perceived by the public as being effective and harmless, and are commonly used for self medication without supervision. In addition, potential interactions between herbal medicines and conventional drugs may compromise with patient management. In the safety evaluation of most substances, non human primates are preferred to rodent species for preclinical animal safety studies, because of their biological similarity to humans. They are regarded to be the best metabolic models for humans in a broad range of investigations. Additionally, a disadvantage of using small animal species in toxicological testing is that they require higher doses of drugs and more frequent administrations than in larger species. In light of these considerations, vervet monkeys are used here to investigate toxicity of a plant-derived triterpene, oleanolic acid. The focus is to determine effects of different concentrations of this triterpene on the cardiovascular, hematopoetic, hepatic and renal systems. Materials and methods: 12 male vervet monkeys used in this study were equally divided into four groups, i.e. three treatment groups (4, 10 and 25 mg/kg bodyweight), and one control group. Each individual in a treatment group received a specified concentration of oleanolic acid in food for 16 weeks. Monkeys in the control group received the vehicle (food) alone. Bodyweight, body temperature, respiratory rate, heart rate, systolic pressure, diastolic pressure, and mean arterial pressure were recorded from ketamine-anaethetized monkeys at baseline and every second week until week 16. In addition, blood samples were collected at baseline and every fourth week for clinical biochemistry indicators (serum electrolytes, enzymes, proteins, lipids, nitrogenous compounds, bilirubins and glucose) and hematological tests (red cell count and its indices, hemoglobin, haematocrit, white blood cell and differential count and platelet count). Results: No animal showed deviation from their normal behavioral patterns, food and water intake, was in poor health or died during and after completion of the study. The average bodyweights were not statistically significantly different between controls and the treated groups. The biphasic changes in the average body temperature of treated monkeys were similar to those seen in the control group during the first eight weeks of the study. No statistically significant differences were found in body temperature determinations between controls and the treated groups. Fluctuations observed in the respiratory rates of the treated monkeys were not statistically significantly different from that of the control group. Although not statistically significantly different from the controls, the systolic, diastolic and mean arterial pressures in the group treated with 25 mg/kg oleanolic acid were lower at week 16 compared to baseline, while those of the groups treated with 4 and 10 mg/kg oleanolic acid were relatively unchanged. Except for a reduction in systolic pressure of the control group, other blood pressure parameters were stable. Heart rates in the treated groups were not statistically significantly different from those in the controls. In all groups, except the control, high density lipoprotein concentrations were higher at week 16 compared to baseline. Fluctuations in low-density lipoprotein and total cholesterol concentrations were similar between controls and the treated groups. The triglycerides were lower at week 16 compared to baseline for all four groups. Upward trends from baseline to the end of the study were observed in creatine kinase concentrations of the controls and the groups that received 4 and 25 mg/kg. Concentrations of this enzyme were unchanged in the group that received 10 mg/kg oleanolic acid between baseline and the end of the study. No statistically significant differences were found with cholesterol, triglyceride and creatine kinase concentrations between treated groups and the controls. Serum concentrations of aspartate aminotransferase were unchanged in the controls and the groups treated with 4 and 10 mg/kg oleanolic acid, but changes in this parameter over time were statistically significantly different (P = 0.0452) from the controls in the group that received 25 mg/kg oleanolic acid. Despite wide fluctuations in the alanine aminotransferase concentrations in the groups that received 4 and 25 mg/kg oleanolic acid, no statistically significant differences were found with any of the treated groups compared to the controls. No statistically significantly different changes were seen in alkaline phosphatase activities between controls and the treated groups. Reductions in gamma-glutamyl transferase activities in the groups that received 4 and 25 mg/kg oleanolic acid were not statistically significantly different from concentrations of this enzyme in the controls. In addition, no statistically significant differences were evident between controls and the group that received 10 mg/kg oleanolic acid. There were no statistically significantly different changes in the total and conjugated bilirubin and glucose concentrations between controls and the treated groups. Fluctuations over time in the serum albumin and globulin concentrations were similar between treated groups and the controls, whereas total protein concentrations were relatively constant. Consequently, no statistically significant differences were found between controls and the treated groups. Wide fluctuations were observed in the creatinine concentrations of the groups that received 4 mg/kg oleanolic acid, while no such changes were encountered in the controls and the group that received 10 and 25 mg/kg oleanolic acid. Serum urea concentrations increased in all groups over time, except for the group that received 10 mg/kg oleanolic acid. Both urea and creatinine concentrations in the treated groups were not statistically significantly different from concentrations in the controls. Serum concentrations of sodium, chloride, potassium, calcium and magnesium and phosphate in the treated groups were not statistically significantly different from these electrolyte concentrations in the controls. Decline in red cell and hemoglobin concentrations of the controls and the group that received 25 mg/kg oleanolic acid were not statistically significantly different between these groups. In addition, no statistical significant differences were found in red cell and hemoglobin concentrations between controls and the groups that received 4 and 10 mg/kg oleanolic acid. Controls and the treated groups showed upward trends in haematocrit concentrations. Mean corpuscular volumes were statistically significantly increased; P = 0.0027 (4 mg/kg), P = 0.0010 (10 mg/kg), and P = 0.0022 (25 mg/kg), while mean corpuscular hemoglobin concentrations were statistically significantly reduced; P = 0.0017 (4 mg/kg), P = 0.0004 (10 mg/kg), P = 0.0002 (25 mg/kg) in the treated groups as compared to the controls. No statistically significant differences were evident in the concentrations of mean corpuscular hemoglobin between controls and the treated groups. White blood cell counts of the treated groups were not statistically significantly different from those of the controls throughout the study period. No statistically significant differences were found in the differential white cells and platelet counts between treated groups and the controls. Discussions: The results of this study showed that administration of oleanolic acid had no effects on the general wellbeing, bodyweights, body temperature, respiratory and heart rates, and blood pressure of vervet monkeys. A statistically significant increase in the aspartate aminotransferase activity of the group treated with 25 mg/kg oleanolic acid, together with the increase in the alanine aminotransferase levels during the same time period, might indicate oleanolic acid-induced hypersensitivity, and accordingly hepatocellular alteration. However, since serum concentrations of these enzymes returned to baseline levels, as well as the absence of variations over time in other parameters of the hepatic function, particularly alkaline phosphatase activity, it is likely that there was no underlying subacute liver disease. Serum renal function parameters also appeared to be within normal physiological limits. No pronounced changes were observed in the hematological parameters of monkeys that received oleanolic acid. Conclusion: This study's results, suggest that oleanolic acid does not produce cumulative liver enzyme alterations, and has no detrimental effects on the renal, hematopoetic and cardiovascular systems of vervet monkeys.